IMPACT OF INDONESIA GOVERMENT POLICY IN PP NO. 27 OF 2021 CONCERNING THE IMPLEMENTATION OF THE MARINE AND FISHERIES SECTOR - Aceng Asnawi Rohani; Mohamad Fasyehhudin; Belardo Prasetya Mega Jaya (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
Government Regulation Number 27 of 2021 concerning the implementation of fisheries and marine affairs is one of the results of discussions to realize a national strategic plan for Indonesia in fisheries and marine affairs. However, in its implementation, it turns out that there are pros and cons in the community. The objective of this research is to analyze the impact of the enactment of Government Regulation Number 27 of 2021 concerning the implementation of the Marine Affairs and Fisheries Sector in realizing the national strategic plan in the marine and fisheries sector by comparing two sides between the government and the community. The results of this research indicate that there are differences of opinion from the Government side which states that Government Regulation Number 27 of 2021 concerning the Implementation of the Fisheries and Marine Affairs has a positive impact on marine and fisheries aspects in Indonesia. Nevertheless, from the community side, it states that there is a negative impact for the benefit and welfare of the people on environmental sustainability. Keywords: Fisheries and Marine; Indonesia Government Policy; National Strategic Plan; Polivy impact.